Grandes projetos e transformações sociais: os efeitos provocados pela mineradora Galvani no município de Lagamar MG - Silva, João Fernandes da (2011)
This research is the result of a survey mostly conducted in Lagamar - MG to detect the opinion of people who are directly and indirectly involved with the city both in the countryside and in town. The work aims at showing the definition of Large Projects in the conception of different authors, and the definition of Territory and the changes caused due to the installation of Galvani Miner in Lagamar in 1996. The concepts used gave theoretical support to the understanding of the effects of large investments from several points of view. The impacts on the city will be revealed, both on social/economic issues and changes on space. A historical and geographical survey of Lagamar is presented, and the main concerns of the population about a possible end of the extraction and the changes to occur are focused as well.